Transcription and initiation of ColE1 DNA replication in Escherichia coli K-12. - Inoue, N (1991)
By S1 nuclease protection mapping, we characterized RNA transcripts and nascent ColE1 DNA synthesized in wild-type Escherichia coli cells after infection with lambda-mini-ColE1 hybrid bacteriophages. Transcription of the RNA II region of ColE1 DNA in vivo starts mostly from the RNA II promoter, which was identified by in vitro experiments, and ends at or near the ori site. Synthesis of the leading strand of ColE1 DNA was found to start at the ori site. Nevertheless, the molar ratio of the nascent DNA to the synthesized transcripts ending at the ori site was less than 0.05. In bacterial rnh mutants whose RNase H activities were less than 0.06% of that of the wild type, transcription patterns, as well as nascent DNA synthesis, were still similar to those in rnh+ cells. However, in bacteria whose rnh gene was interrupted by insertion of a drug resistance gene, the number of transcripts ending at the ori site was much reduced and that of transcripts reading through the ori site was definitely increased relative to that observed in wild-type bacteria. These results suggested that cleavage of the RNA transcript at the ori site in vivo is dependent on RNase H activity, as demonstrated in the in vitro system, but most of the cleaved RNA is unable to prime initiation of ColE1 DNA synthesis efficiently.